Altered Electrolyte Homeostasis and the Severity of Dengue in Children - Tayyaba Anwar; Heena Rais; Saba Safdar; Shaista Ehsan (ziauddin University, 2024)
Background: Dengue is the commonest arboviral disease that is endemic in our country. Electrolyte imbalance is commonly encountered in this disease. There had been only a few worldwide research studies investigating at all the metabolic parameters of dengue infection. Therefore, the study aimed to assess the electrolyte imbalance and its correlation with the severity of dengue fever in pediatrics. Methods: This cross-sectional study was carried out in the Pediatric Department of Ziauddin Hospital over 18 months. Diagnosed patients through detection of Dengue NS1 antigen or serology of dengue fever from 6 months to 18 years of age were enrolled and their history, hematological and electrolyte values (sodium, potassium, calcium, magnesium, and phosphate) were analyzed. Data was analyzed by SPSS and a Chi-squared test was used to compare the frequency of electrolyte disturbances between patients. A p-value <0.05 was considered statistically significant. Results: A higher incidence of dengue fever was observed in the younger age group (81)54 %. The majority of the patients showed mild hyponatremia 82(54.6%), mild hypokalemia 63(42%) and hypocalcemia 96(64 %). Hypophosphatemia 98(65.3 %) (p-value 0.045) was found more compared to hypomagnesemia 22(14.6%). Fever was observed in 100% of patients along with body aches 90(60%), drowsiness 31(20.7%) and abdominal pain 16(10.7%). We also found leucopenia 48(32%) and thrombocytopenia 127(84.6%), whereas hematocrit 30(20 %) was also raised. Conclusion: Majority of electrolytes (sodium, potassium, calcium and phosphate) were found decreased in dengue patients. However, hyponatremia (p=0.001) and hypophosphatemia (p=0.045) were significantly associated to the severity of dengue. Keywords: Dengue; Severe Dengue; Electrolytes; Hyponatremia; Hypokalemia.